How Relevant is Size for Setting the Scope of The IFRS for SMEs? - Catalin Nicolae Albu (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) is currently considered for adoption by national regulators in many emerging economies and a few developed countries. The cost-benefit approach is advanced as useful to investigate how the scope of the IFRS for SMEs should be set. Size is used in many jurisdictions as criterion to set financial reporting obligations, but it is questioned if it represents an appropriate criterion for the scope of the IFRS for SMEs. The aim of this paper is therefore to empirically investigate the applicability and consequences of using various criteria to set the scope of IFRS for SMEs, and to discuss the implications of using size instead of other criteria. Data consists of a sample of 194 questionnaires completed by accountants employed by Romanian SMEs. I find that the choice between size and other criteria is related to placing greater emphasis on preparers or users, or on costs versus benefits. Also, findings suggest that while size is correlated with users-based criteria, the level of agreement between various criteria for setting the scope of the standard is medium. Therefore, in order to capture the cost-benefit tension two criteria might be used in deciding the scope of the standard.
Keywords: M41; M48; 650; IFRS for SMEs; emerging economies; Romania; quantitative criteria